2003
DOI: 10.1074/jbc.m213220200
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the DNA Binding Activity of the TATA-binding Protein Renders the Transcriptional Function of Rvb2p/Tih2p, the Yeast RuvB-like Protein, Essential for Cell Growth

Abstract: In Saccharomyces cerevisiae, two highly conserved proteins, Rvb1p/Tih1p and Rvb2p/Tih2p, have been demonstrated to be major components of the chromatinremodeling INO80 complex. The mammalian orthologues of these two proteins have been shown to physically associate with the TATA-binding protein (TBP) in vitro but not clearly in vivo. Here we show that yeast proteins interact with TBP under both conditions. To assess the functional importance of these interactions, we examined the effect of mutating both TIH2/ R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 60 publications
(83 reference statements)
1
39
0
Order By: Relevance
“…Ino80 is recruited to at least two yeast promoters, and either activates or represses a large number of genes, presumably by mobilizing nucleosomes and altering the accessibility of the underlying DNA to the transcription machinery (19,20). As expected, Reptin is required for the correct expression of many of the same genes (20); other studies showed a significant overlap between the genes controlled by Pontin and those controlled by Reptin (18,(31)(32)(33). This demonstrates that Reptin and Pontin play a role in activation and repression and suggests that they function in the same complex (but see also the section on gene repression below).…”
Section: Pontin and Reptin And Chromatin Remodeling Complexesmentioning
confidence: 91%
See 1 more Smart Citation
“…Ino80 is recruited to at least two yeast promoters, and either activates or represses a large number of genes, presumably by mobilizing nucleosomes and altering the accessibility of the underlying DNA to the transcription machinery (19,20). As expected, Reptin is required for the correct expression of many of the same genes (20); other studies showed a significant overlap between the genes controlled by Pontin and those controlled by Reptin (18,(31)(32)(33). This demonstrates that Reptin and Pontin play a role in activation and repression and suggests that they function in the same complex (but see also the section on gene repression below).…”
Section: Pontin and Reptin And Chromatin Remodeling Complexesmentioning
confidence: 91%
“…Independently from the experiments described above, Pontin and Reptin were also identified by virtue of their physical interaction with the transcription-associated protein β-Catenin (44,45), and with the transcription factors TBP (32,(45)(46)(47), Myc (48), E2F1 (only Pontin; 49) and ATF2 (only Reptin; 50). Subsequently, Pontin and/or Reptin were shown to bind to the promoters of transcriptional targets of c-Myc (51, 52), E2F1 (52) and NFκB (53), often along with components of the Tip60 complex.…”
Section: Transcriptional Repression By Reptin (And Pontin)mentioning
confidence: 99%
“…Tah1 is suggested to function as a co-chaperone of Hsp90 in disaggregating Pih1 (6). As shown in Figure 1, it has been determined that Rvbs are involved in many different cellular processes such as transcriptional regulation, DNA repair, telomerase assembly, and mitotic spindle assembly (7)(8)(9)(10)(11)(12), in contrast, when in complex with Tah1 and Pih1, R2TP's cellular function is limited to apoptosis, PIKK signaling, snoRNP biogenesis, and RNA polymerase II assembly ( Figure 1) (2-4, 12, 13). Also, R2TP (or at least Rvbs) is found in ASTRA (ASsembly of Tel, Rvb and Atm-like kinase) complex which is suggested to be involved in telomere maintenance and TORC1 signaling in yeast (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three other proteins that were found to bind the N terminus of c-Myc share residence with Tip48 and Tip49 in the Ino80 (BAF53 and ␤-actin) (24) or Tip60 complex (transformation͞transcription-domain-associated protein, BAF53, and ␤-actin) (24, 25). Further support for an involvement of Tip48 and Tip49 in transcription is provided by the observations that both proteins colocalize with c-Myc on the nucleolin promoter (26) and that elimination of Tip48 or Tip49 function in yeast rapidly affects the expression of a large number of targets (16,27,28). Such a transcriptional role is also consistent with the described genetic interactions between a tip48 mutation and ␤-catenin in zebrafish and interactions of tip48 and tip49 with a ␤-catenin-reporter system in Drosophila (11,29); in both of these in vivo interactions, Tip48 behaved as a negative component and Tip49 behaved as a positive component of the Wg signaling cascade.…”
mentioning
confidence: 99%
“…Different observations strongly suggest that one major function of the Tip proteins resides in the control of transcription. Initially, vertebrate Tip49 was found to be a Tata-binding protein-interacting protein (13)(14)(15)(16); later Tip48 and Tip49 were also shown to interact physically with the different transcription factors ␤-catenin (11,14), c-Myc (12), E2F1 (only Tip49) (17), and ATF2 (only Tip48) (18), raising the possibility that the Tip proteins could bridge basic transcription machinery and sequence-specific activators. Both proteins were also purified as part of several multiprotein complexes involved in transcriptional regulation: the Ino80 chromatin remodeling complex in yeast (19,20), Polycomb repressive complex 1 in Drosophila (only Tip48) (21), the Tip60 HAT complex in vertebrates (22), and the Uri complex regulating nutritiondependent gene expression in yeast and in vertebrates (23).…”
mentioning
confidence: 99%